VALLEJO, I. (2019). El infinito en un junco: la invención de los libros en el mundo antiguo. Madrid: Siruela. - Sain, Abril Sofia (Daimon Revista Internacional de Filosofia, 2022)
Reseña de: VALLEJO, I. (2019). El infinito en un junco: la invención de los libros en el mundo antiguo. Madrid: Siruela.